Evaluate the Mean Effect of Oral 25% Glucose Solution for Pain Relief in Term Infants, as Compared with Control Group, During Venipuncture - Mehmood, Usama Rana; Ahmed, Zeeshan; Saeed Zaman Khattak; Tabussam, Samina; Ayla Ahmad Jaspal (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the efficacy of 25% oral glucose solution in providing analgesia as compared to control group in fullterm neonates undergoing venipuncture. Study Design: Quasi-experimental study.Place and Duration of Study: Department of Paediatrics, Pak-Emirates Military Hospital, Rawalpindi Pakistan, from Nov 2021 to Apr 2022.Methodology: A total of 112 neonates born at full-term requiring venipuncture were included in our study. Neonates who required more than one prick per cannulation, those who couldn’t tolerate oral feeding, or had received opiates, sedatives or NSAIDs since birth were excluded. All patients underwent venipuncture, however, patients in Group A received oral 25% glucose solution while those in Group B received breast milk. All patients were scored according to the NIP score at 1-, 5- and 10-minutes post venipuncture. Data was analyzed by SPSS 26.0.Results: The patients in our sample had a mean age of 2.85±1.24 days, of whom males were 67(59.8%). The average time taken per venipuncture was 30.11±6.65 seconds. There was no difference between the two groups at baseline in terms of NIPS. In addition, no statistical difference between the two groups post-procedure in terms of NIPS was seen at 1-, 5- and 10-minutes post-venipuncture (p=0.201, p=0.411 and p=0.454, respectively).Conclusion: The use of oral 25% glucose solution can be used a comparable substitute to breast milk in the provision of analgesia for neonates who have trouble with lactation, while undergoing venipuncture.